(untitled) (Nigerian Journal of Technology, 2023)
Abstract There are several gravity reductions approaches that are available for use in geodetic applications. More so, with the rapid rate at which gravimetric geoid models are being incorporated into GNSS solutions, the need for precise regional models is becoming increasingly relevant. In this study, two gravity reduction approaches (Bouguer and Residual Terrain Model (RTM)) have been used to reduce gravity anomalies over Ado town. The reduced anomalies were then used to compute a local geoid for the study area using the conventional Stokes integral in the RCR technique. Comparison of the computed geoid by both methods with GNSS Levelling data at selected locations show that the RTM reduced anomalies produce a better geoid model than the Bouguer reduced anomalies over the study area with a RMSE of 83.2cm and 83.5cm respectively. Keywords: Long wavelength Geoid, Stokes Integral, Remove Compute Restore, Potential Field